seco-Irldoids from Calycophyllum spruceanum (Rubiaceae) - Zuleta, LMC; Cavalheiro, Alberto José [UNESP]; Silva, DHS; Furlan, Maysa [UNESP]; Young, MCM; Albuquerque, S.; Castro-Gamboa, I; Bolzani, Vanderlan da Silva [UNESP] (Elsevier B.V., 2003)
Three seco-iridoids 7-methoxydidcrrosidc, 6'-O-acetyldiderroside and 8-O-tigloyldiderroside, were isolated from the wood bark of Calycophyllum spruceanum together with the known iridoids loganetin, loganin and the seco-iridoids secoxyloganin, kingiside and diderroside. Their structures were elucidated by means of NMR and MS spectral data analysis. Using NOE correlations and coupling constants, the relative stereochernistry of the new derivatives was established. 7-Methoxydiderroside, 6'-O-acetyldiderroside and the known secoxyloganin and diderroside showed in vitro activity against trypomastigote forms of Trypanosonla Cruzi, with IC50 values of 59.0, 90.2, 74,2 and 84.9 mug/mL, respectively and were compared to the standard gentian violet (IC50 7.5 mug/ml). (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Calycophyllum spruceanum; Rubiaceae; iridoids; seco-iridoids; antitrypanosomal activity